2012
DOI: 10.1080/02699931.2011.613919
|View full text |Cite
|
Sign up to set email alerts
|

Depression and rumination: Relation to components of inhibition

Abstract: Results highlight the importance of differentiating among components of inhibition to gain a better understanding of cognitive mechanisms underlying depression and rumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 24 publications
4
70
0
1
Order By: Relevance
“…That is, although Zetsche et al (2012) found that depressed participants (vs. control participants) experienced greater interference from irrelevant negative words given a positive target, they found no such association in another study (Zetsche & Joormann, 2011).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…That is, although Zetsche et al (2012) found that depressed participants (vs. control participants) experienced greater interference from irrelevant negative words given a positive target, they found no such association in another study (Zetsche & Joormann, 2011).…”
mentioning
confidence: 87%
“…Although it has been postulated that attentional control would also be associated with rumination (Koster et al, 2011), Zetsche and colleagues found this relationship to be elusive when using the emotional flanker task. In one study, Zetsche et al (2012) found no relationship between attentional bias for negative words and rumination, whereas in another study, Zetsche and Joormann (2011) found the counterintuitive result that rumination was associated with less interference from negative word distracters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, found a significant genetic factor shared among MDD, GAD, and PD that was independent from the genetic influences of neuroticism, and found that only about 25% of the genetic correlation between MDD and GAD was shared with neuroticism, leaving a considerable amount of shared genetic variation to be explained by other factors. We propose that the comorbidity among the disorders in the INT-AM subfactor are explained by a genetic predisposition for various interrelated negative thought (NT) processes that have empirical links to depression and anxiety, including attentional biases to threatening and sad stimuli, excessive contemplation of negative information, difficulty shifting attention away from 21 negative information, and trouble suppressing pessimistic cognitions (e.g., Bradley, Mogg, White, Groom, & de Bono, 1999;Everaert, Koster, & Derakshan, 2012;Gotlib & Joormann, 2010;Hirsch, Clark, & Mathews, 2006;Mathews & MacLeod, 2005;Mogg, Philippot, & Bradley, 2004;Vanderhasselt, et al, 2012;Zetsche, D'Avanzato, & Joormann, 2012). This predisposition underlies cognitive characteristics of these disorders, like worry, rumination, hopelessness, and negative attributions about the self and the future (e.g., Alloy et al, 2004;Nolen-Hoeksema, Wisco, & Lyubomirsky, 2008;Papageorgiou, 2006), as well as anhedonia and low levels of positive affect which are also characteristics of these disorders (Krueger, 1999a;Watson, 2005).…”
Section: Negative Thought Processes Liability Twin Studies Have Demomentioning
confidence: 99%
“…For example, induced attentional bias to threat stimuli predicts subsequent engagement in worry (Hirsch et al 2011), and high levels of worry are associated with inefficient filtering of threat-related memories (Stout et al 2015). Similarly, rumination is linked to deficits in working memory in healthy individuals and decreased ability to inhibit irrelevant information in those with depression (Zetsche et al 2012), and cognitive inhibition has been proposed as a key impairment underlying engagement in rumination (Joormann 2010). These findings suggest that deficits in executive function may diminish cognitive control over emotional processes, which may lead to increased engagement in worry and rumination.…”
Section: Introductionmentioning
confidence: 98%